SELECTIVE STUDY OF ORGANIC COMPOUNDS AS CORROSION INHIBITORS OF COPPER, ALUMINIUM AND STEEL SALINE WATER (ARTIFICIAL SEA WATER) - Llanos Ch., Bertha (2002)
With electrochemical, weight loss tests and superticial analysis with near infrared spectroscopy (NIR) and scan electronic microscopy (SEM), were selectivity at 5-aminotetrazol with 90.4 % of efficiency to aluminium and 90.8 % of efficiency to copper and the cupferron for steal with 87.8 % of efficiency such as corrosion inhibitor for synthetic sea water.